Aerial Observations of Symmetric Instability at the North Wall of the Gulf Stream. Issue 1 (8th January 2018) - Savelyev, I.; Thomas, L. N.; Smith, G. B.; Wang, Q.; Shearman, R. K.; Haack, T.; Christman, A. J.; Blomquist, B.; Sletten, M.; Miller, W. D.; Fernando, H. J. S.
Abstract: An unusual spatial pattern on the ocean surface was captured by thermal airborne swaths taken across a strong sea surface temperature front at the North Wall of the Gulf Stream. The thermal pattern on the cold side of the front resembles a staircase consisting of tens of steps, each up to ∼200 m wide and up to ∼0.3°C warm. The steps are well organized, clearly separated by sharp temperature gradients, mostly parallel and aligned with the primary front. The interpretation of the airborne imagery is aided by oceanographic measurements from two research vessels. Analysis of the in situ observations indicates that the front was unstable to symmetric instability, a type of overturning instability that can generate coherent structures with similar dimensions to the temperature steps seen in the airborne imagery. It is concluded that the images capture, for the first time, the surface temperature field of symmetric instability turbulence. Key Point: Aerial thermal imagery collected at Gulf Stream's boundary reveals fine structure of the front's breakdown due to symmetric instability